The association of lipids and novel non-statin lipid-lowering drug target with osteoporosis: evidence from genetic correlations and Mendelian randomization - Qingcong Zheng; Rongjie Lin; Du Wang; Rongsheng Chen; Weihong Xu (BMC Musculoskeletal Disorders)
Abstract Background It remains controversial whether lipids affect osteoporosis (OP) or bone mineral density (BMD), and causality has not been established. This study aimed to investigate the genetic associations between lipids, novel non-statin lipid-lowering drug target genes, and OP and BMD. Methods Mendelian randomization (MR) method was used to explore the genetic associations between 179 lipid species and OP, BMD. Drug-target MR analysis was used to explore the causal associations between angiopoietin-like protein 3 (ANGPTL3) and apolipoprotein C3 (APOC3) inhibitors on BMD. Results The IVW results with Bonferroni correction indicated that triglyceride (TG) (51:3) (OR = 1.0029; 95% CI: 1.0014–1.0045; P = 0.0002) and TG (56:6) (OR = 1.0021; 95% CI: 1.0008–1.0033; P = 0.0011) were associated with an increased risk of OP; TG (51:2) (OR = 0.9543; 95% CI: 0.9148–0.9954; P = 0.0298) was associated with decreased BMD; and ANGPTL3 inhibitor (OR = 1.1342; 95% CI: 1.0393–1.2290; P = 0.0093) and APOC3 inhibitor (OR = 1.0506; 95% CI: 1.0155–1.0857; P = 0.0058) was associated with increased BMD. Conclusions MR analysis indicated causal associations between genetically predicted TGs and OP and BMD. Drug-target MR analysis showed that ANGPTL3 and APOC3 have the potential to serve as novel non-statin lipid-lowering drug targets to treat or prevent OP.